Conservative versus surgical management of pediatric bipartite patella with patellar dislocation: a single-center retrospective analysis - Wang, Xipeng; Nie, Kun; Liu, Jiangtao (Frontiers in Surgery, 2026)
ObjectiveTo evaluate clinical features and compare outcomes of conservative vs. surgical management in pediatric patients with congenital bipartite patella (BP) and patellar dislocation.MethodsA retrospective study included 42 children (≤16 years) with BP and patellar dislocation treated between January 2019 and January 2024. Patients received either conservative treatment (n = 18; reduction, immobilization, and rehabilitation) or surgical treatment [n = 24; lateral retinacular release, medial patellofemoral ligament (MPFL) reconstruction, ± internal fixation of accessory fragments]. Functional outcomes were assessed using Lysholm, Kujala, and visual analog scale (VAS) scores preoperatively and at final follow-up. Radiological parameters included patellar congruence angle, tibial tubercle–trochlear groove distance, and accessory fragment healing. Complications and recurrence rates were recorded.ResultsBaseline characteristics were comparable, except for a higher proportion of having suffering recurrent dislocations in the surgical group (P = 0.001). Both groups improved significantly in functional scores (P < 0.05), but the surgical group demonstrated superior outcomes (Lysholm: 90.5 ± 4.8 vs. 76.3 ± 8.1; Kujala: 92.1 ± 3.9 vs. 78.9 ± 7.5; VAS: 1.2 ± 0.9 vs. 3.1 ± 1.4; P < 0.001). Surgical patients achieved normalization of patellofemoral alignment, and all eight patients undergoing internal fixation achieved solid bony union. Recurrence occurred in 27.8% of conservatively treated patients but in none of the surgical group. No major complications were reported.ConclusionIn pediatric BP with patellar dislocation, surgical management combining MPFL reconstruction and lateral retinacular release, with selective internal fixation, provides superior functional recovery, pain relief, and lower recurrence compared to conservative therapy, suggesting that surgical management may provide superior outcomes in selected pediatric patients.